2017
DOI: 10.21037/cdt.2017.03.09
|View full text |Cite
|
Sign up to set email alerts
|

Screening echocardiograms in a senior focused value based primary care improves systolic heart failure detection and clinical management

Abstract: Background: Screening echocardiograms are not indicated. Our aim is to evaluate the impact of screening echocardiograms on improving clinical management among older adults.Methods: We performed screening echocardiograms for all consecutive patients and defined incident systolic heart failure (HF) as an ejection fraction of less than 50% among patients without a previous HF diagnosis. We reviewed medical record data to determine if the new cases where Stage B or C. We obtained prescribed medications and vital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…We have previously found that screening echocardiograms identify stage B heart failure and when this information was shared with the physician there were medication changes and improved outcomes and costs. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously found that screening echocardiograms identify stage B heart failure and when this information was shared with the physician there were medication changes and improved outcomes and costs. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…High-touch care with frequent preventative visits with primary care provider and specialists has been shown to result in higher use of cardiovascular medications, fewer hospitalizations and lower healthcare costs. 8 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…However, neither the American College of Cardiology nor the American Heart Association recommend screening echocardiograms for asymptomatic at-risk patients. We have previously shown that screening echocardiograms identify patients with previously unknown asymptomatic heart failure 6 and patients with unknown diastolic heart failure. 5 We also showed that identifying patients at higher risk leads to better cardiovascular risk factor control and better outcomes.…”
Section: Sudden Death Risk Score Prediction and Addition Of Echocarmentioning
confidence: 99%
“…The American College of Cardiology and the American Heart Association do not recommend screening echocardiograms in patients without heart disease unless there is a genetic predisposition to cardiomyopathy . However, echocardiograms in asymptomatic consecutive primary care patients have been able to identify new cases of heart failure (HF) and grade 3 diastolic dysfunction leading to changes in management . Therefore, the aim of our study is to evaluate if echocardiographic parameters in primary care patients can improve the ability of the SCD risk score to identify patients at risk of death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation